COOLMATH4KIDS WEBSITE ON BASIC MATHEMATICAL OPERATIONS FOR GRADE III STUDENTS OF ELEMENTARY SCHOOL - amri, muhammad; Kusmawati, Heny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics is often considered a difficult and boring subject for elementary school students. This situation encourages teachers to seek more engaging and effective learning media. One technology-based media that can be utilized is the Coolmath4Kids website, which provides interactive materials and games to help students understand basic math concepts in a fun way. This study aims to describe the strategy for utilizing the Coolmath4Kids website in teaching basic arithmetic operations to third-grade students at MI Hidayatul Islam Gembong, as well as to analyze the positive and negative impacts of its use. The uniqueness of this study lies in its focus on the context of an elementary madrasah with limited technological facilities. However, this limitation actually encourages teachers to be more creative in utilizing existing technology optimally. This study employed a descriptive qualitative approach, employing field research. Data were obtained from third-grade teachers, students, and the principal as primary sources, and supporting documents as secondary sources. Data collection techniques included direct observation and in-depth interviews. The research results show that the Coolmath4Kids utilization strategy was implemented in three stages. First, the planning stage involved developing objectives based on CPL and ATP, selecting features, and setting up the projector. Second, the implementation stage included explaining the material, observing with students, and taking turns answering questions. Third, the evaluation stage involved practice questions and evaluations by teachers and the principal. The use of Coolmath4Kids has had positive impacts, including increased student enthusiasm, easier conceptual understanding, and a more enjoyable learning environment. However, there have been negative impacts, including language barriers, students' focus sometimes shifting to games, and limited internet connection.